1999
DOI: 10.1002/(sici)1097-0142(19991225)87:6<380::aid-cncr9>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of fine-needle aspiration cytology in the evaluation of metastatic clear cell tumors

Abstract: BACKGROUND Clear cell tumors (CCTs) occur as primary neoplasms in a number of anatomic sites. Due to their overlapping morphologic features, these tumors can be challenging for the cytologist, particularly when they present as metastatic lesions. METHODS Forty‐nine fine‐needle aspirations (FNA) of metastatic CCTs from 46 patients (age range, 29–87 years; mean, 64 years) were reviewed retrospectively. In addition to the routine smears and cell block preparations, ancillary studies were performed in selected cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 20 publications
0
39
0
Order By: Relevance
“…H&E stain (ϫ40, ϫ100); B Tg stain (ϫ40, ϫ100); C TTF-1 stain (ϫ40, ϫ100); D PAS stain (ϫ40, ϫ200) Thyroglobulin staining is the most sensitive immunohistochemical tool for distinguishing between primary thyroid carcinomas and metastases from carcinomas arising in other organs. 7,9,13,15,18,22 Interestingly, Shimizu et al 7 and Carcangiu et al 14 suggested that Tg staining might be weak or unclear, even in tumors derived from thyroid follicular cells, although they noted that such findings were uncommon. Shimizu et al 7 correlated the results of Tg staining with those of periodic acid-Schiff (PAS) staining and concluded that these combinations identify primary clear cell tumors of the thyroid more sensitively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…H&E stain (ϫ40, ϫ100); B Tg stain (ϫ40, ϫ100); C TTF-1 stain (ϫ40, ϫ100); D PAS stain (ϫ40, ϫ200) Thyroglobulin staining is the most sensitive immunohistochemical tool for distinguishing between primary thyroid carcinomas and metastases from carcinomas arising in other organs. 7,9,13,15,18,22 Interestingly, Shimizu et al 7 and Carcangiu et al 14 suggested that Tg staining might be weak or unclear, even in tumors derived from thyroid follicular cells, although they noted that such findings were uncommon. Shimizu et al 7 correlated the results of Tg staining with those of periodic acid-Schiff (PAS) staining and concluded that these combinations identify primary clear cell tumors of the thyroid more sensitively.…”
Section: Discussionmentioning
confidence: 99%
“…22 Subsequent immunohistochemical staining with thyroglobulin (Tg) is helpful for distinguishing between primary and metastatic thyroid carcinomas. 7,9,13,15,18,22 We used both Tg and thyroid transcription factor-1 (TTF-1) stains to confirm the RCC metastasis. TTF-1, a homeodomain containing the nuclear protein originally identified in thyroid follicular cells, has been evaluated as an immunohistochemical marker for the identification of thyroid or lung tissue.…”
mentioning
confidence: 99%
“…6 However, in the case of an unknown primary, differentiation of renal cell carcinoma from hepatocellular carcinoma can be difficult and rarely indistinguishable by light microscopy alone, especially with clear cell and granular cell variants. 7 In this case, the smears demonstrate classic features of hepatocellular carcinoma, including the trabecular arrangements with prominent endothelial cells, resemblance to normal hepatocytes, but with marked increased nuclear to cytoplasmic ratios and large nucleoli. The yellow granules (bile) and monolayers transgressed by capillaries greatly aid in the diagnosis.…”
Section: Discussionmentioning
confidence: 70%
“…[11] Fuhrman nuclear grade used in histology can be applied in cytology smears. [14] Cells of RCC contain intra cytoplasmic fat, hence Oil Red O staining of air dried smears can be used to distinguish RCC from other clear cell tumors. [15] While metastasis are associated with poor outcome, solitary bone lesions have increased associated survival when compared to multiple bony lesions or a combination of bone and other organs.…”
Section: Discussionmentioning
confidence: 99%